Femtosecond laser induced nano-textured micropatterning to regulate cell functions on implanted biomaterials. (15th October 2020) - Seo, Youngmin; Kim, Saeromi; Lee, Hyun Soo; Park, Jaeho; Lee, Kyungwoo; Jun, Indong; Seo, Hyunseon; Kim, Young Jin; Yoo, Youngsik; Choi, Byoung Chan; Seok, Hyun-Kwang; Kim, Yu-Chan; et al.
Abstract: Posterior capsular opacification (PCO) is the most common complication of cataract surgery. PCO is due to the proliferation, migration, and epithelial-to-mesenchymal transition of the residual lens epithelial cells (LECs) within the lens capsule. As surface topography influences cellular response, we investigated the effect of modulating the dimensions of periodic nano-textured patterns on the surface of an intraocular lens material to regulate lens epithelial cell functions such as cell adhesion, migration, orientation, and proliferation. Patterned poly(HEMA) samples were prepared by a femtosecond laser microfabrication, and the behaviors of human B-3 LECs were observed on groove/ridge patterns with widths varying from 5 to 40 µm. In the presence of ridge and groove patterns, the adherent cells elongated along the direction of the patterns, and f-actin of the cells was spread to a lesser extent on the nano-textured groove surfaces. Both single and collective cell migrations were significantly inhibited in the perpendicular direction of the patterns on the nano-textured micro-patterned samples. We also fabricated the patterns on the curved surface of a commercially available intraocular lens for in vivo evaluation. In vivo results showed that a patterned IOL could help suppress the progression of PCO by inhibiting cell migration from the edge to the center of the IOL. Our reports demonstrate that nano- and microscale topographical patterns on a biomaterial surface can regulate cellular behavior when it is implanted into animals. Graphical Abstract: Image, graphical abstract